Fluorescence emission enhancement of a T-shaped benzimidazole with a mechanically-interlocked 'suit'. Issue 26 (1st March 2021) - Xu, Houyang; Lin, Meng-Di; Yuan, Jun; Zhou, Baiyang; Mu, Yingxiao; Huo, Yanping; Zhu, Kelong
Abstract : Enhanced fluorescence emission of a T-shaped benzimidazole axle that is mechanically interlocked in a suit[1]ane. Abstract : A fluorescent T-shaped benzimidazole was successfully designed and interlocked in a bicyclic macrocycle to form a suit[1]ane through supramolecular templated-synthesis. Compared with the bare fluorophore, suit[1]ane requires nearly two times the concentration to initialize the aggregation-caused quenching effect in solution. Furthermore, an 8-fold higher solid-state fluorescence quantum yield (21.7%) is also achieved. By taking advantage of mechanical bonding and molecular packing, such fluorescence emission enhancement through formation of a suitane opens the way to new complex fluorescent materials.